Private banking, banking legislation and banking centralization between 1870 and 1923 in Colombia - Lesmes, Pedro José (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this article is to show the legal process of private banking, which originated in Colombia during the period of Liberal Radicalism (1863-1886). With the rise of the Regeneration in 1886, its advance over the country the Presidential Centralism, of Catholic and authoritarian court, would directly affect the interests of bankers, merchants and producers who used the benefits of free banking. With the arrival of the regenerating government, bankers will be forced into the laws imposed since centralization, the imposition of monetary policies and credit policies. The methodology used is qualitative and seeks to analyze the regulations, problems and difficulties that occurred in Colombia between 1870 and 1923. It was noted that given the difficulties in organizing the banking system in Colombia, it was necessary to establish controls with greater severity. Private Banks, for example, the Kemmerer Mission in 1922, which raised the need to centralize the country's banking system, thus giving rise to the Bank of the Republic, with functions of the Central Bank and regulating private banks by means of the Banking Superintendence.